1976
DOI: 10.1002/1097-0142(197612)38:6<2232::aid-cncr2820380607>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy in advanced lung cancer with increased survival

Abstract: Twenty-eight patients with lung cancer, 26 with extensive disease, were treated with the drugs Cytoxan (Cyt) and methotrexate (MTX). The schedule was based on cellular kinetics concepts. Initial therapy was with Cyt 1.1 g/m2 (intravenously) followed by MTX 20 mg/m2 orally, twice weekly, started 9 days later, when the tumor was considered to be most susceptible to an S-phasespecific drug. The course was repeated at three-week intervals. Based on dose response curves, Cyt and MTX dose modifications were individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some bacterial proteins were demonstrated to induce host cell pathology by subcellular targeting, and some of these proteins have an NLS sequence. The cytolethal distending toxins of Gram‐negative bacteria such as Escherichia coli , Campylobacter sp , and Actinobacillus actinomycetemcomitans induce cell cycle arrest at the G2/M phase transition by nuclear targeting and ultimately induce cell death . The outer membrane protein A (AbOmpA) of Acinetobacter baumannii induces endonucleolytic attack of chromosomal DNA after nuclear translocation .…”
mentioning
confidence: 99%
“…Some bacterial proteins were demonstrated to induce host cell pathology by subcellular targeting, and some of these proteins have an NLS sequence. The cytolethal distending toxins of Gram‐negative bacteria such as Escherichia coli , Campylobacter sp , and Actinobacillus actinomycetemcomitans induce cell cycle arrest at the G2/M phase transition by nuclear targeting and ultimately induce cell death . The outer membrane protein A (AbOmpA) of Acinetobacter baumannii induces endonucleolytic attack of chromosomal DNA after nuclear translocation .…”
mentioning
confidence: 99%
“…This pattern was reflected in the results of each investigative procedure and underlines the difficulties in interpreting the results of therapeutic trials based on cytological or biopsy diagnoses of large cell carcinoma. 21 In any classification there has to be a group in which to place cases that cannot be classified into any of the other better-defined groups. In the context of this paper the undifferentiated large cell group is this residual group.…”
mentioning
confidence: 99%
“…64 The median survival of patients with metastatic bone disease is between 3 and 9 months. 65 Loblaw et al 66 found the median survival Epidural spinal cord compression is usually associated with inadequate control of the primary tumor, and the goal of treatment is palliative and directed at maintaining ambulation, decreasing tumor bulk, and relieving pain. 67 Those patients who develop spinal cord compromise secondary to metastatic disease often can be palliated effectively with short-course external beam radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…64 The median survival of patients with metastatic bone disease is between 3 and 9 months. 65 Loblaw et al 66 found the median survival from diagnosis of spinal cord compression for patients with lung cancer was 1.5 months and only 4.2% of patients survived 1 year. This study also demonstrated that cancer patients who had spinal cord compression in the last year of life spent twice as many days in the hospital than those who did not have spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%